Put To The Test: Strength Shoes: Warm-up with Strength Shoes lacks performance benefit - Sands, W. A.; McNeal, J. R.; Henderson, H. L.; Poole, R. C. (1999)
At recent women`s track and field competitions, including the NCAA national championships and earlier meets at Brigham Young University, athletes have been seen using the Strength Shoe (SS) as a warm-up device prior to sprinting and jumping events. We sought to investigate the effect of the SS on sprint and jump performance following warm-up with and without the SS. Elite collegiate female track and field sprinters and jumpers (N = 12, 21 ± 2.2 yr, 171.2 ± 7.8 cm, 62.0 ± 6.6 kg) were alternately assigned to experimental (EXP) and control (CON) conditions. The tests consisted of 20-m flying sprint (20FS) and vertical jump (VJ) tests in a repeated measures, crossover-design experiment. Athletes performed a self-selected general warm-up for approximately 15 minutes, followed by the treatment warm-up consisting of 10 double-leg bounds, 10 single-leg bounds on each leg, and 10 vertical jumps. During the treatment warm-up, CON athletes wore their normal track shoes while EXP athletes wore the SS. Following warm-up, the EXP athletes wore their normal track shoes. Athletes performed three trials of a running single-leg VJ using a jump and reach apparatus (CON = 0.99, EXP = 0.98), and three trials of the 20FS (CON = 0.97, EXP = 0.96). One week later, the EXP and CON group assignments were exchanged and the protocols were repeated. Matched-pairs t-tests were calculated to determine whether the warm-up with the SS increased VJ height or 20FS speed. The results showed that warm-up using the SS did not improve performance in either the VJ (t[11] = -1.08, p = 0.303) or the 20FS (t[11] = 0.28, p = 0.79). Warm-up with the SS does not appear to have an effect on subsequent sprint or jump performance.